Etiology of severe acute respiratory infections in children hospitalized in hospitals of Ekaterinburg in the epidemic season of 2022 — 2023 - E. V. Lelenkova; I. A. Korotkova; A. Yu. Markaryan; E. V. Bolgarova; A. E. Chernysheva; P. I. Filatova; A. V. Semenov (Детские инфекции (Москва))
Objective. Study of the viral etiology of severe acute respiratory infections (SARI) in children hospitalized in a hospital in Yekaterinburg during the epidemic season of 2022—2023. Materials and methods. 267 clinical samples (nasopharyngeal swab) obtained from children hospitalized with symptoms of acute respiratory disease were studied. The etiology of the disease was deciphered by RT-PCR, using standard sets of reagents. The material was examined for the presence of influenza A and B viruses, as well as for viruses of non-influenza etiology. 267 individual patient records were analyzed. Results. As a result, it was found that cases of SARI were more often registered among younger children, the structure of SARI of influenza etiology was represented by influenza A(H1N1)pdm09 virus — 29.9% and influenza B virus — 20.7%, while it was found that most children were not vaccinated against influenza. The proportion of viruses of non-influenza etiology was represented by RS viruses (23.0%), rhinoviruses (9.2%) and bokaviruses (6.3%).